Potential role of Lu/BCAM in HIV-related atherosclerosis - Modisa S. Motswaledi; Ishmael Kasvosve; Oluwafemi O. Oguntibeju (African Journal of Laboratory Medicine, 2019)
Atheromatous lesions are formed by macrophages and low-density lipoprotein cholesterol invading the vascular intima. Here we show that increasing cholesterol levels are associated with peripheral monocyte depletion and this imbalance is aggravated by carriage of Lu/BCAM leukocyte adhesion molecules. This is true only in HIV infection and probably explains the risk of atherosclerosis observed in HIV-positive patients.